A Muslim wife's right to seek dissolution of her marriage and her rights after a divorce: a study of the Malaysian law with special reference to the State of Selangor / Nik Elin Zurina Nik Abdul Rashid - Nik Abdul Rashid, Nik Elin Zurina (Faculty of Law, 1984)
Marriage is a sacrament, as well as a contract in Muslim family Law, and like every contractual agreement it can be terminated on several grounds. i.e. through divorce, annulment, the death of either party or by a decree from the courts. Divorce however, is, "of all things permitted, the one most detestable to God” and a lot of steps are taken in order to discourage a divorce, but as it is against the restriction of liberty of men and women, Islam may only check hasty actions by arbitrators or a Judge, leaving the doors to reconciliation open at many stages, for instance a period of eddah, has to be observed.